Penyelesaian Sengketa Hak Waris Anak Angkat Dalam Perspektif Hukum Positif - Muhammad Yasir; Gunawan Hadi Purwanto; Herawati Herawati (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Inheritance disputes involving adopted children are often a complex issue in legal practice in Indonesia, given the lack of comprehensive uniformity of arrangements between Western civil law, Islamic law, and customary law. This study aims to examine how Indonesia's positive law regulates the position of adopted children in terms of inheritance and dispute resolution mechanisms arising from claims of inheritance rights of adopted children. The normative juridical approach is used by examining various laws and regulations such as the Civil Code, the Child Protection Law, and the Compilation of Islamic Law (KHI), accompanied by case studies of court decisions. The results of the study show that in Western civil law, adopted children have an equal legal status with biological children in terms of inheritance, while in the perspective of KHI, adopted children do not automatically obtain inheritance rights, but can be given a mandatory will. Dispute resolution is carried out through litigation and non-litigation channels such as mediation, taking into account the principles of justice and protection of children. Therefore, legal harmonization and regulatory reform are needed to ensure legal certainty for adopted children in the context of inheritance